2022
DOI: 10.1007/s11192-022-04473-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Covid-19 on publications in economics: bibliometric evidence from five working paper series

Abstract: We compare Covid-related working papers in economics to non-Covid-related working papers in four dimensions. Based on five well-known working papers series and data from the RePEc website, we find that Covid papers mainly cover topics in macroeconomics and health, they are written by larger teams than non-Covid papers, are more often downloaded and they receive more citations relative to non-Covid papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This pattern can be largely explained by the Corona pandemic, which started in early 2020. The onset of the crises triggered an immediate output of papers dealing with health issues (Bürgi & Wohlrabe, 2022;Kruger, Maturana, & Nickerson, 2023;Thomson, Mosier, & Worosz, 2023). In 2020 and 2021, there are 3,966 papers (about 5% of all papers in these years) including at least one of the words 'pandemic', 'Corona' or 'COVID' in the abstract.…”
Section: Publication Counts In 'Production and Organizations' (D2)mentioning
confidence: 99%
“…This pattern can be largely explained by the Corona pandemic, which started in early 2020. The onset of the crises triggered an immediate output of papers dealing with health issues (Bürgi & Wohlrabe, 2022;Kruger, Maturana, & Nickerson, 2023;Thomson, Mosier, & Worosz, 2023). In 2020 and 2021, there are 3,966 papers (about 5% of all papers in these years) including at least one of the words 'pandemic', 'Corona' or 'COVID' in the abstract.…”
Section: Publication Counts In 'Production and Organizations' (D2)mentioning
confidence: 99%
“…Although there are reviews in the literature that deal with themes associated with economic processes and their implications in general terms, productions that specifically deal with agricultural commodities in the light of interdependence or the effect of contagion are scarce in the literature. Some bibliometric studies associated with economics can be found, addressing: the most cited journals in economics [22], field normalization and citation impact time in economics [23], academic entrepreneurship [18], agricultural production [24], the interference of COVID-19 in publications in economics [25], green economy focusing on economic and environmental factors [26] and the accounting literature since the financial crisis of 2008-2009 [27].…”
Section: Introductionmentioning
confidence: 99%